Large-scale demand response and its implications for spot prices, load and policies: Insights from the German-Austrian electricity market - Märkle-Huß, Joscha; Feuerriegel, Stefan; Neumann, Dirk (Applied energy, 2018)
•We model the large-scale impact of demand response systems with real-world data.•Our key measures include electricity price, grid load and financial savings.•The average spot price, as well as the peak price, decrease considerably.•However, the volatility of the price can rise, impairing non-flexible customers. Active load shifting of the electricity demand unlocks a variety of benefits. Examples of such advantages include the increased stability of energy systems, reduced electricity costs and financial savings in the transmission as well as generation infrastructure. Although the technology necessary for demand response has been extensively studied for individual appliances or at the micro-grid level, evaluations of its nationwide impact are scarce. Yet governments and policy-makers require quantitative assessments in order to understand the underlying value and derive appropriate policies. For this purpose, this paper utilizes real-world data from the German-Austrian electricity market in order to calculate ex post the impact of demand response on electricity spot prices and load. As a result, we find that a 25% adoption rate of the available potential for load shifting could have decreased nationwide electricity expenses by approximately €500million, or 6%, in 2014. At the same time, we observe that the price volatility rises under this scheme and thus impairs non-flexible electricity customers. This observation entails significant implications in terms of designing effective policies.